Arts-Based Engagement Ethnography: An Approach for Making Research Engaging and Knowledge Transferable When Working With Harder-to-Reach Communities. Issue 1 (18th January 2019) - Goopy, Suzanne; Kassan, Anusha
In social science research, epistemological assumptions regarding what constitutes valid research fall into two main areas of inquiry—qualitative and quantitative. Within a qualitative paradigm, eliciting a close and often intimate exploration of phenomenon from a text-based or verbal approach is privileged, and in a quantitative paradigm, obtaining a systematic, large population survey or questionnaire approach is prioritized. Although the two are not mutually exclusive, with the development of each, the visual and the kinesthetic aspects have both largely been lost. This article proposes an arts-based engagement ethnography (ABEE) as a means of reclaiming these visual and kinesthetic aspects in order to engage in culturally sensitive research with underrepresented communities. To this end, this article outlines some of the limitations of current research and explores how cultural probes (a set of simple items given to participants to help them document their experiences) can be used to enter qualitative research from a different epistemological vantage point. Moreover, this article discusses the use of qualitative interviews and focus groups in ABEE and the manner in which this methodology allows for unique knowledge mobilization possibilities. It highlights how these are built into the research design, and how this is an important part of the approach's ability to engage harder-to-reach communities.